2014
DOI: 10.1111/j.1532-950x.2014.12300.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Rima Glottidis Area and Lack of Laryngeal Epiglottic–Glottic Seal After Unilateral Cricoarytenoid Lateralization Ex Vivo

Abstract: Unilateral arytenoid lateralization results in some degree of LEGS with a misalignment of the epiglottis over the RG. Our results revealed that the optimal RGA associated with the minimal LEGS was obtained with dorsal placement of a cricoarytenoid suture when the cricothyroid joint and the interarytenoid band were intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…14,[21][22][23]26,27 Over the years, the literature has shifted practice away from procedures which dramatically increase the RGA to those that provide a moderate increase in order to lessen the risk of aspiration through better preservation of the LEGS. 11,14,20,21,23,27 The Hagen-Poiseuille equation describes the impact of airway radius on the physics of laminar gas flow, principally, that airway resistance is inversely proportional to the airway radius to the fourth power. Based on our results, the average increase in RGA following a TEA would equate to an estimated 84% decrease in airway resistance using this calculation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…14,[21][22][23]26,27 Over the years, the literature has shifted practice away from procedures which dramatically increase the RGA to those that provide a moderate increase in order to lessen the risk of aspiration through better preservation of the LEGS. 11,14,20,21,23,27 The Hagen-Poiseuille equation describes the impact of airway radius on the physics of laminar gas flow, principally, that airway resistance is inversely proportional to the airway radius to the fourth power. Based on our results, the average increase in RGA following a TEA would equate to an estimated 84% decrease in airway resistance using this calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Across these UAL techniques, there was an average increase in RGA of 180.07% (173.68–186.45), while the TEA yielded an average 157.00% (Table 1). Many studies evaluating surgical treatment for canine laryngeal paralysis have shown that only a small increase in RGA is required to provide relief of clinical signs 14,21–23,26,27 . Over the years, the literature has shifted practice away from procedures which dramatically increase the RGA to those that provide a moderate increase in order to lessen the risk of aspiration through better preservation of the LEGS 11,14,20,21,23,27 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations